Anteseden Impulsive Buying Intention Pada Gen Z Pengguna Tiktok Live Streaming di Jakarta - Matulatuwa, Marsha Anthina; Briliana, Vita (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this study is to understand the effect of combining factors such as Demand (D), Convenience (C), Interactivity (I), Playfulness (P), and Perceived Usefulness (PU) that effect Perceived Enjoyment (PE), as well as the relationship between Impulsive Buying Intention (IBI) in Generation Z TikTok Live Streaming users in Jakarta. The object used in this study is TikTok Live Streaming users. The method used to select samples in this study was Purposive Sampling, with a sample size of 360 respondents who are TikTok Live Streaming users. Structural Equation Modelling Partial Least Square (SEM PLS) 4.0 and IBM SPSS29 were used to test the data obtained. The results obtained in this study indicate that there is a positive influence between the variables D, C, I, P, and PU on PE, as well as the variables D, C, I, P, PU, and PE on IBI. In addition, the variables D, C, I, P, and PU also have a positive effect on IBI which is mediated by PE Generation Z TikTok Live Streaming users in Jakarta.